SOCIAL MEDIA AS A MARKETING MEANS OF EDUCATIONAL INSTITUTIONS IN THE MODERN ERA - Jannah, Faridatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze and understand about Social Media as a Means of Marketing Educational Institutions. Along with the development of technology, social media has become one of the means of communication and information of the community. Social media is also used as a promotional tool for an organization by utilizing existing features. Educational institutions that use social media as a means of promotion can show the advantages and programs that exist in educational institutions so that they can attract prospective students or guardians of students to study at the institution. The role of social media in promoting educational institutions. The research method used is literature research. This research method is to collect information and data through scientific writing or the collection of information of a literary nature that is relevant to the research subject, or to study and solve problems in depth based on relevant library materials The result of this research is that social media can be used to promote educational institutions effectively and efficiently. Because in social media applications there are features that can be set according to the desired target, so that the messages contained in the promotional content are conveyed to people in need. In addition, promotion through social media can lead to education both directly and indirectly.